Measuring Urban Heat Islands Using Landsat 8 TIRS and Investigating the Variety of Landuse Proportion in Yogyakarta City - Puspita, Belinda Duhita; Hadiyanti, Amalia (Proceeding International Conference on Religion, Science and Education, 2022)
Urban Heat Islands (UHIs) are one of the challenges that have emerged from urbanization and climate change in Yogyakarta. As the city grows more urbanized, the buildings and population also become denser which therefore reduces the availability of open space including green areas. This research aims to determine the variety of Land Surface Temperature (LST), UHI intensity distribution, and the proportion of landuse (vegetation and non-vegetation area) based on UHI intensity class. The LST and UHI intensity was derived from Landsat 8 Thermal Infra-Red Sensor (TIRS) satellite image of 2018 processed by LST algorithm method. The landuse proportion was obtained by analyzing the pixel samples (30x30m) on google earth image, UHI intensity class, and LST map. The results show that Yogyakarta is dominated by the high surface temperature (37° - 42°C). In general, non-UHI areas are located on the outside of the city bordering the Regencies of Sleman and Bantul, while the high intensity of UHI is in urban activity centers which are dominated by non-vegetated areas. The highest UHI intensity, 5.41°C, indicates the high-temperature difference between UHI and the non-UHI surrounding areas. The high intensity of UHIs is caused by the dominance of built-up areas (settlement, public building, and road). The results of sample identification in the non-UHI intensity class showed the proportion of 43.91% vegetation and 56.09% non-vegetation (roads). Meanwhile, the high UHI intensity class showed a proportion of 100% non-vegetation (built-up area).